2019
DOI: 10.1002/ar.24143
|View full text |Cite
|
Sign up to set email alerts
|

Call for a Multidisciplinary Effort to Map the Lymphatic System with Advanced Medical Imaging Techniques: A Review of the Literature and Suggestions for Future Anatomical Research

Abstract: This review intends to rekindle efforts to map the lymphatic system by using a more modern approach, based on medical imaging. The structure, function, and pathologies associated with the lymphatic system are first discussed to highlight the need for more accurately mapping the lymphatic system. Next, the need for an interdisciplinary approach, with a central role for the anatomist, to come up with better maps of the lymphatic system is emphasized. The current approaches on lymphatic system research involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 111 publications
1
8
0
Order By: Relevance
“…Interestingly, in another recent study to visualize the cisterna chyli, using the latex and barium sulphate mixture, Renard et al showed that retrograde injection of the thoracic duct was in fact possible, despite the presence of the valves (Renard, de Mestier, et al, ). This finding is in accordance with previous findings from our research group (Degen, Van de Velde, & Van Hoof, ; Stouthandel et al, ).…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…Interestingly, in another recent study to visualize the cisterna chyli, using the latex and barium sulphate mixture, Renard et al showed that retrograde injection of the thoracic duct was in fact possible, despite the presence of the valves (Renard, de Mestier, et al, ). This finding is in accordance with previous findings from our research group (Degen, Van de Velde, & Van Hoof, ; Stouthandel et al, ).…”
Section: Introductionsupporting
confidence: 94%
“…T8‐T12, thoracic vertebra 8–12; VA, vena azygos; VH, vena hemi‐azygos. Adapted from Stouthandel et al ()…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that mercury injections can no longer be performed, thus not allowing the replication of these historical works and the fact that historical anatomists did not have a lot of faith in microscopes yet in the 1800s, as evidenced by entries such as "his observation having been made with very high magnifying powers, are not exempt from a portion of doubt which seems almost inseparable from results so obtained" [59], would suggest that it is high time that the lymphatic system anatomy is re-evaluated. This time, the historical anatomical drawings can even be objectified by using modern medical imaging techniques that will be able to capture the contrast-filled lymphatics in relation to the regional anatomy [60].…”
Section: Techniques To Characterise Breast Lymphatic Anatomymentioning
confidence: 99%
“…Instead, atlas plates are likely made up of several different specimens, maybe even combining data from adult and child/foetal specimens in the same plates. As it is not possible to confirm how many specimens were used for the construction of a certain atlas plate, plates could be based on only one or two specimens and anatomical variability might be severely underrepresented, making a re-examination of these historical works all the more relevant today, now that we have the technological means to objectively capture the results [60].…”
Section: Techniques To Characterise Breast Lymphatic Anatomymentioning
confidence: 99%